Industrial symbiosis and agri-food system: Themes, links, and relationships - Hamam, Manal; Spina, Daniela; Raimondo, Maria; Di Vita, Giuseppe; Zanchini, Raffaele; Chinnici, Gaetano; Tóth, József; D'Amico, Mario (Frontiers in Sustainable Food Systems, 2023)
Industrial symbiosis is an eco-innovative system concept that is based on a circular economy and industrial ecology ideas. This process comprises the movement of materials, energy, and skills across enterprises located within eco-industrial parks, and strives to provide economic, environmental, and social competitive advantages for all the involved parties. Considering that the agri-food system creates a vast quantity of by-products along the supply chain, it is a sector that has huge potential within material and energy recovery systems and fits well into eco-industrial parks. The current study is a literature review that aims to evaluate the interest exhibited so far by scientific research in the topic of industrial symbiosis in the agri-food sector and to highlight the primary analytical techniques that have been used for this topic. Using the paradigm of multiple correspondence analysis, a content analysis was conducted from which the major themes of the researched phenomena emerged. The results indicate that the topic areas are unrelated and somewhat distant from each other. The analysed case studies have revealed that the authors had neglected the communicative and collaborative elements among stakeholders, and instead focused on the potential use of some tools and approaches. Furthermore, it has been hypothesised that the hiding of information within a supply chain prevents industrial symbiosis procedures from being implemented. This research suggests the necessity of creating communication and cooperation platforms among stakeholders, which would promote the introduction of new techniques and tools for the development of circular production systems.